Surgery for metastases for esophageal-gastric cancer in the real world: Data from the AGAMENON national registry. Issue 8 (August 2018) - Carmona-Bayonas, Alberto; Jiménez-Fonseca, Paula; Echavarria, Isabel; Sánchez Cánovas, Manuel; Aguado, Gema; Gallego, Javier; Custodio, Ana; Hernández, Raquel; Viudez, Antonio; Cano, Juana María; Martínez de Castro, Eva; Macías, Ismael; et al.
Abstract: Introduction: The effect of surgery for metastases in patients with esophagogastric cancer is unknown, given the lack of randomized clinical trials; likewise, the criteria for selecting eligible patients remain to be determined. Methods: This registry evaluates the results of patients with advanced adenocarcinoma of the stomach, distal esophagus, or gastro-esophageal junction from 32 centers. To assess selection criteria and prognostic factors, a state arrival extended Markov proportional hazards (PH) model was used. Results: 1792 subjects were analyzed, 5% of whom (n = 92) underwent surgery for metastasis. The most common surgeries were peritoneal (29%), hepatic (24%), and distant lymph nodes (11%). Subjects chosen for metastasectomy had higher survival rates, HR 0.34 (95% CI, 0.06–0.80, p  = 0.021). Patients who underwent surgery had a mOS since metastasectomy of 16.7 months (95% CI, 12.5–22.4). The 1- and 3-year relapse rates following R0 resection were 58% and 65%, respectively. Median time since R0 metastasectomy until relapse was 8.4 months (95% CI, 7.6–23.7). The 3-year OS after surgery was 30.6% (95% CI, 19.3–40.4). Duration of chemotherapy prior to surgery (months) increased mortality (HR 1.04 [95% CI, 1.01–1.07]), p  = 0.009. The only significant interaction involved the use of anti-HER2 therapy. Conclusion: The AGAMENON registry suggests that subjects with limited metastatic disease, selected on a clinical basis, can benefit from early surgeries. Prospective trials are needed to confirm these data.